Capitalization of Religion in Online Ta'aruf Accounts - Ahmad Zainal (Jurnal Al-Hikmah, 2024)
Taaruf as a "religious" way of introduction is often associated with the most "syar'i" pre-wedding process. Perhaps this is true, but this depiction was apparently used by the accounts @komuniastaarufku, @taaruf_id, and @belajartaaruf to gain commercial interests. This research will look at the extent to which Islamic ideas in taaruf accounts emerge in the context of reification. After that, the reification of these ideas became a form of religious capitalization. By using netnographic data mining methods, this research can answer these objectives comprehensively. Based on the research that has been carried out, the idea of ??taaruf appears to be expressed in a reification of marriage. Taaruf is only used as an intermediary for the concept of marriage, which is always presented in the biological realm, so it reduces the essence of marriage itself. Apart from that, taaruf accounts also cover these offers with the hashtags hijrah, sunnah, halal, etc., as part of "good design" to make them look more Islamic. Such forms of reification are, of course, aimed at the capitalization process so that the taaruf process in these accounts is closely related to the capitalization of religion.